2018
DOI: 10.1080/09603123.2018.1514458
|View full text |Cite
|
Sign up to set email alerts
|

Childhood respiratory allergies and symptoms in highly polluted area of Central Europe

Abstract: The study investigated the associations between the prevalence of the childhood respiratory diseases and the long-term exposure to air pollution in the burdened area of Moravian-Silesian Region in the Czech Republic. The health data were collected during 2014 in 7,239 children 5, 9, 13 and 17 years of age. Exposure to PM and NO in the residence addresses was based on dispersion models and GIS based traffic-related indicators. PM levels were positively associated with both lifetime (OR 1.35; 95%CI 1.09-1.67) an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 28 publications
0
6
0
Order By: Relevance
“…Nitrogen dioxide (NO 2 ) is an air pollutant discharged from combustion of human activities such as driving cars, and numerous epidemiological studies have suggested a relationship between NO 2 and impaired respiratory function or asthma symptoms [1][2][3][4].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nitrogen dioxide (NO 2 ) is an air pollutant discharged from combustion of human activities such as driving cars, and numerous epidemiological studies have suggested a relationship between NO 2 and impaired respiratory function or asthma symptoms [1][2][3][4].…”
Section: Introductionmentioning
confidence: 99%
“…An exogeneous variable was included in each SARIMAX model 2. Coefficients in log scale for exogeneous variable 3. O 3 /AO were used for the analyses at AAPMSs/RAPMSs, respectively.…”
mentioning
confidence: 99%
“…The association was stronger for one-year exposure (OR 1.37 for NO 2 and 1.32 for NOx), and lower for lifetime asthma (OR NO 2 1.09 and NOx 1.08) in children. For the latter (lifetime asthma), Puklová et al (2019) found no associations (OR 0.86 for NO 2 ), and the prevalence of current asthma OR with NO 2 was around 0.93 in children, being EMEP the DM model. Their results differ from the association of prevalence found in for NOx, which was OR 1.20 for adults, being USEPA ISC the DM used.…”
Section: Nitrogen Oxides (No X )mentioning
confidence: 77%
“…There have been numerous studies on asthma exacerbation due to exposure to ambient air pollutants. However, relatively few studies have employed dispersion models to understand the role of ozone (O 3 ) Fridell et al, 2014;Tsui et al, 2018), particulate matter (PM), mainly PM 10 Pénard-Morand et al, 2010a) and PM 2.5 (Batterman et al, 2014b;Jiřík et al, 2017;Levy et al, 2002), nitrogen oxides (NO x ) Puklová et al, 2019), carbon monoxide (CO) (Batterman et al, 2014a;, sulfur dioxide (SO 2 ) (Koiwanit et al, 2016;Milando et al, 2016;Pascal et al, 2013) and volatile organic compounds (VOC) (Charpin et al, 2009;Spadaro and Rabl, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, it is hardly surprising that out of 29 AR cases co-occurring with bronchial asthma, 19 people participating in our study were sensitive to these agents. It is assumed that yearround allergens are the most common cause of bronchial asthma, while the seasonal allergens are most often associated with the development of AR [40,41]. It is also known that about 10-30% of rhinitis develops into bronchial asthma, and one factor predisposing to this unfavorable progression is severe rhinitis, among others, especially in the course of allergy to year-round allergens, such as house dust mites [42,43].…”
Section: Discussionmentioning
confidence: 99%